2007
DOI: 10.1111/j.1399-3054.2007.01005.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a type A response regulator in the common bean (Phaseolus vulgaris) in response to phosphate starvation

Abstract: Type A response regulators are a family of genes in Arabidopsis thaliana involved primarily in cytokinin signal transduction. A member of this family was isolated from a cDNA library constructed from bean plants (Phaseolus vulgaris) grown under conditions of phosphate starvation. The complete cDNA sequence showed the presence of the DDK domain, which is the hallmark of the response regulator family. Expression of the P. vulgaris response regulator 1 (PvRR1) showed clear regulation based on phosphate availabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…We have identified genes that are up-regulated in Pistarvation conditions, and some of them encode proteins that are involved in signal transduction (Camacho et al, 2008;Martinez et al, unpublished data). One of these proteins has high homology with the catalytic subunit of the AMPK from mammalian cells and with the catalytic subunit of the Snf1 from yeast.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have identified genes that are up-regulated in Pistarvation conditions, and some of them encode proteins that are involved in signal transduction (Camacho et al, 2008;Martinez et al, unpublished data). One of these proteins has high homology with the catalytic subunit of the AMPK from mammalian cells and with the catalytic subunit of the Snf1 from yeast.…”
Section: Discussionmentioning
confidence: 99%
“…These late genes generally increase the acquisition of Pi or promote the efficient use of Pi within the plant (Vance et al, 2003). In bean (Phaseolus vulgaris) plants, we identified early and late genes that encode proteins that might be involved in signal transduction (Camacho et al, 2008;P. Coello, A. Ramírez, and E. Martínez-Barajas, unpublished data).…”
mentioning
confidence: 96%
“…Specific members of a group of regulatory histidine kinases, ARRs, have also been suggested as mediators of P‐responses, as ARR6 (At5g62920) (Coello and Polacco 1999) and homologues in bean (Camacho et al 2008) are responding to P starvation. However, these regulators do not appear to be P‐specific.…”
Section: Regulation Of the Plant P‐starvation Responsementioning
confidence: 99%
“…The expression of some type-A ARRs genes is regulated by various environmental stresses, nitrogen levels and phosphate starvation [45], [46], [47]. Our study showed that cytokinin substantially increased the transcript level of RcRR1 .…”
Section: Discussionmentioning
confidence: 54%